Dexmedetomidine improves gastrointestinal motility after laparoscopic resection of colorectal cancer: A randomized clinical trial. Issue 29 (July 2016) - Chen, Chaojin; Huang, Pinjie; Lai, Lifei; Luo, Chenfang; Ge, Mian; Hei, Ziqing; Zhu, Qianqian; Zhou, Shaoli
Abstract: Background: To investigate the effects of intraoperative application of dexmedetomidine (Dex) on early gastrointestinal motility after laparoscopic resection of colorectal cancer. Methods: In this prospective, randomized double-blind investigation, 60 patients who underwent laparoscopic resection of colorectal cancer were randomly allocated to receive Dex (DEX group, n = 30) or saline (CON group, n = 30). In the DEX group, Dex was loaded (1 μg/kg) before anesthesia induction and was infused (0.3 μg/kg/h) during surgery. Time to postoperative first flatus (FFL) and first feces (FFE), and time to regular diet were recorded. Serum diamine oxidase (DAO) activity and intestinal fatty acid-binding protein (I-FABP) were detected. Results: Both the time to the FFL (44.41 ± 4.51 hours vs 61.03 ± 5.16 hours, P = 0.02) and the time to the FFE (60.67 ± 4.94 hours vs 82.50 ± 6.88 hours, P = 0.014) were significantly shorter in the DEX group than the CON group. Furthermore, the time to regular diet of the DEX group was shorter than that of the CON group (76.15 ± 4.11 hours vs 91.50 ± 5.70 hours, P = 0.037). Both DAO and I-FABP increased significantly from beginning of surgery to postoperative day 1 in the CON group (2.49 ± 0.41 ng/mL vs 4.48 ± 0.94 ng/mL for DAO, P = 0.028, 1.32 ± 0.09 ng/mL vs 2.17 ± 0.12 ng/mL for I-FABP, P = 0.045, respectively), whereas no significant change was observed in the DEX group. Furthermore, patients in the DEX group had stable hemodynamics and shorter hospital stay than those in the CON group. Conclusion: Dex administration intraoperatively benefits recovery of gastrointestinal motility function after laparoscopic resection of colorectal cancer with stable hemodynamics during surgery though further studies are needed to explore the mechanisms of Dex on gastrointestinal motility.